1984
DOI: 10.1530/acta.0.1070155
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic testing of prolactin and growth hormone secretion in patiens with neuroendocrine disorders

Abstract: Prolactin (Prl) and growth hormone (GH) responses to different pharmacologic probes acting at the central nervous system (CNS) or the anterior pituitary (AP) level were evaluated in patients with distinct neuroendocrine disorders. Thirteen patients with Prl-secreting tumours (PST), 10 acromegalics (A) and 8 patients with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 13 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…A severe reduc¬ tion in adrenal size and function within 2 years of MPA treatment was noted sooner than previously reported in dogs treated with MPA for 45 months (Frank et al 1979). The failure of TRH to in¬ crease GH in acromegalie dogs contrasts with the increased GH observed in the majority of acrome¬ galie humans injected with TRH (Müller et al 1984). …”
Section: Discussionmentioning
confidence: 95%
“…A severe reduc¬ tion in adrenal size and function within 2 years of MPA treatment was noted sooner than previously reported in dogs treated with MPA for 45 months (Frank et al 1979). The failure of TRH to in¬ crease GH in acromegalie dogs contrasts with the increased GH observed in the majority of acrome¬ galie humans injected with TRH (Müller et al 1984). …”
Section: Discussionmentioning
confidence: 95%
“…Sex steroids are regarded as capable of stimulating GH secretion [4], The postpartum period is important for the induction of lactation. It follows pregnancy with its high levels of circulating steroids which continue to condition hypo thalamo-pituitary activity [5][6][7], The importance of high prolactin (Prl) levels during this period is well known. Increasing during pregnancy, plasma Prl levels reach a maximum before delivery [8,9], The best-known action of Prl in humans is the induction and maintenance of lac tation [10,11], Prl secretion is inhibited by dopamine (DA) release by T1DA system neurons.…”
Section: Introductionmentioning
confidence: 99%
“…The same favorable prognostic value of a TRH positive response has been found in the prolactin secreting pituitary adenomas. 27 It is not possible from this study to determine if this "paradoxical" response to TRH is due to a liberation of GH stored in intracytoplasmic granules of tumor cells or is the result of increased synthesis of GH in those cells; however, since it was found that intracytoplasmic granules are more abundant in the cells of those TRH positive cases, it is possible that "paradoxical" TRH response results from the liberation of previously stored GH. In vitro studies in prolactin secreting pituitary adenomas in regard to PRL secretion, indicate that the positive response to TRH is probably due to an increased release of PRL from cell granules.…”
Section: Discussionmentioning
confidence: 79%